Strategi Satuan Pengawas Internal untuk Meminimalisasi Temuan (Studi kasus pada Perguruan Tinggi Keagamaan Islam Negeri A) - Helti Nur Aisyiah (Universitas Bina Sarana Informatika, 2019)
This study aims to find out how the internal auditor (SPI) in Islamic College (PTKIN) A works. This research chose SPI PTKIN A due to the achievement of SPI PTKIN A which succeeded in obtaining zero findings on examination object in 2016 previously audited by SPI. Based on the research result, SPI PTKIN A has initiated the concept of pre-audit, current-audit, and post-audit on every activity contained in the working plan and budget of the ministry and institution (RKAKL) of fiscal year 2016. With these three concepts make SPI successfully suppress fraud and minimize the findings.Keywords: audit, internal control unit, fraud, findings